Spiritualitas Pentakosta Berdasarkan Perspektif Liturgi Katolik - Wibowo, Darren Milano; Stevani, Novia (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2024)
AbstractThe Pentecostalism movement has grown so rapidly that its impact and movement is not limited to certain denominations. Even for some Catholic groups, this movement is also practiced by them. This happens because of a deep longing for the movement of the Holy Spirit. The liturgy of worship in Catholicism is considered monotonous and not passionate. So this is enough to trigger the existence of Charismatic Catholicism or what is commonly referred to as "Charismatic Renewal". Charismatic Catholicism does not occur universally, but it already exists in Indonesia and only a few churches recognize and experience it. In detail the author discusses: Pentecostal spirituality in general; Charismatic Catholicism and its history and origins in Indonesia as well as the benefits of the movement; the liturgy of worship in Catholicism; then the differences between Charismatic Catholicism and Charismatic Pentecostalism. Indeed, Pentecostal spirituality is not only for Pentecostals, but also for every church and people of God who long to experience it. The most important key to experiencing this movement is the thirst and longing to experience the movement of the Holy Spirit. So, it is not about certain denominations or groups, but individuals who long to experience a breakthrough, especially in the liturgy of worship. AbstrakGerakan Pentakostalisme mengalami perkembangan yang pesat, sehingga dampak dan pergerakannya tidak hanya terjadi pada denominasi tertentu saja. Bahkan bagi sejumlah kelompok Katolik, gerakan ini juga dilakukan oleh mereka. Hal ini terjadi karena adanya kerinduan yang mendalam akan kegerakan Roh Kudus. Liturgi ibadah dalam agama Katolik dinilai monoton dan tidak bergairah. Sehingga hal ini cukup menjadi pemicu adanya Agama Katolik Karismatik atau yang biasa disebut dengan “Pembaruan Karismatik”. Katolik karismatik tidak terjadi secara universal, namun sudah ada di Indonesia dan hanya sedikit gereja yang mengakui dan mengalaminya. Secara rinci penulis membahas: Spiritualitas Pantekosta secara umum; Katolik Karismatik beserta sejarahnya dan asal usulnya di Indonesia serta manfaat gerakannya; liturgi ibadah dalam Katolik; lalu perbedaan antara Katolik Karismatik dan Pentakosta Karismatik. Sejatinya spiritualitas Pentakosta bukan hanya diperuntukkan bagi kaum Pentakosta saja, namun juga berlaku bagi setiap gereja dan umat Tuhan yang rindu untuk mengalaminya. Kunci terpenting untuk mengalami gerakan ini adalah rasa haus dan kerinduan untuk mengalami gerakan Roh Kudus. Jadi, bukan tentang denominasi atau kelompok tertentu, tapi individu yang rindu mengalami terobosan, khususnya dalam liturgi ibadah.